Durio tanjungpurensis (Malvaceae), a new species and its one new variety from west Kalimantan, Indonesia (Bangladesh Journal of Botany, 2018)
A new species and a new variety of Durio Adanson from West Kalimantan are described namely, Durio tanjungpurensis Z.I. Navia, sp. nov. and D. tanjungpurensis var. tembaganensis Navia, var. nov. The new species has small fruits (5 - 8 cm in diam), brown to yellowish green pericarp, milky white thin aril (